Utilization Of Family Toilet In The Allu Village Of Minasa Baji Bantimurung Districts Of Maros Regency - rahmat panyiwi (Jurnal Ilmiah Kesehatan Sandi Husada, 2018)
Background: One of the efforts to improve community health status is the existence of environmental health facilities that meet health requirements, including the availability of family toilets. The absence of family latrines, or the unavailability of family toilets that meet the requirements in an area, is caused by several things such as insufficient knowledge of the residents, benefits that will be felt if they have a family toilet that meets the requirements. large funds to make eligible family latrines. Method, this type of research is "descriptive" research to find out the use of family latrines. In this study the sample was the head of the family (KK) or those who were able to respond like their wives or children. The sampling technique in this study was "Random Sampling. Results, the level of knowledge lacked a greater chance of not utilizing family latrines fulfilling the conditions, income lacking greater opportunities not utilizing family latrines fulfilling the conditions, lack of greater opportunity not using family latrines fulfilling the requirements. Conclusion of respondents with a less knowledgeable level of opportunity not utilizing family latrines fulfilling the requirements, namely from 33 respondents with less knowledge 27 who did not use family latrines to meet the requirements, respondents with less opportunities did not use family latrines to meet conditions, namely from 37 respondents with attitudes of less than 25 who do not use family latrines to meet the requirements, respondents with less income have a greater chance of not utilizing family latrines to meet the requirements, namely from 26 responds en with an income of less than 17 who do not use family toilets to meet the requirements.